Kajian Pengembangan Layanan Pengguna Jasa Transjakarta pada Rute Cileduk – Tendean - Achmad Hamdy; Realiza Realiza; Anton Ferdiansyah (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2019)
The research objective is to determine the integration between Corridor 13 development planning and the quality of Transjakarta Bus services. Transjakarta Bus Transport is one of the mass transports operating in DKI Jakarta. This research was conducted by providing alternative solutions to problems with the proposed development of facilities located in Corridor 13 of the Ciledug - Tendean route and also the future needs of the fleet to support the smooth operation of Corridor 13 in the future. The research method used quantitative analysis through average waiting times, frequency of public vehicle departures, headway, load factors, and Round Trip Time. To get the benefit for service providers, this research is expected to be a reference for evaluation materials for service providers related to the operation of Transjakarta Corridor 13 Bus route. The sample size used 45 service users as the object of the questionnaire. From the analysis, some solutions can be obtained as in the development plan by adding frequency, headway, and operating hours on Transjakarta operations. For Service Quality, there are efforts to improve facilities and infrastructure facilities for repairing the Platform Screen Door and adding the fans. It is expected that the operator of TransJakarta considers the inputs to anticipate the high expectations of the number of passengers in the coming 5 years.